VAN JAARSVELD, F.A. Inventory of documents - VAN JAARSVELD, F.A. (ARCA, 2018)
Private papers of F.A van Jaarsveld, Professor in History at UNISA [1960-1967], RAU [1967- ] and University of Pretoria.
COVERAGE 1918-1932; 1 File; 1.20 metre
Keywords: VAN JAARSVELD, F.A.; Inventories